The Food Acquisition Program - PAA as a Mitigation Strategy for Food and Nutritional Insecurity in the Life of Family Farmers in Rio Preto da Eva – AM (Research, Society and Development, 2022)
This article aims to evaluate the effects generated in family farming from the operationalization of the Food Acquisition Program - PAA. Seeking to characterize the aspects related to food and nutritional security of family farmers, pointing out indicators that allow a previous diagnosis of reality. For that, we used the case study, where the interviewees were separated into two groups, suppliers and non-suppliers, the results were obtained through the application of socioeconomic forms, a questionnaire on food frequency and the Brazilian Food Insecurity Scale. - EBIA. The scale pointed out the PAA's efficiency in its broadest context, covering from its origins, executions, modalities reaching its peak, demonstrating how it can also be a channel to build food and nutritional security. This understanding has become essential to trace new paths based on the results of the research, in which it highlights important aspects of sustainability with regard to food and nutritional security. Seeking to understand sustainability from the perspective of public policies, especially those that promote the importance of family farming. It is relevant to emphasize that the strengthening of policies aimed at family farming is shown as a sustainability strategy, as well as the insertion of family farming as a rural development strategy.